It’s the People, Stupid! - Formal Models of Social Interaction in Agile Software Development Teams - Corbett, Andrea; Holcombe, Mike; Wood, Stephen (Advances in Social Sciences Research Journal, 2015)
The success of modern ICT systems is not just about the technology. The human and social dimensions are also critical – especially in terms of understanding the context and environment within which the systems operate. This is true also about the environment in which the system is developed. Although much effort has been expended on building and analysing formal models of software systems, little has been done in terms of how software development teams work and how this might be studied in a formally-based way. This research looks at one of the fundamental aspects involved in collaborative teams working in projects – the transactive memory system (TMS). This, well established, concept in psychology is an approach to how the different people in a team regard the capabilities (knowledge and abilities) of each other as it changes over time. These capabilities are the basis for decision making in software projects about who does what, and when. Using a formal model of the TMS of a team, based on agent-based modelling, simulations were made of how teams might operate under different circumstances. The initial model was validated against published data. The model was then investigated in terms of how different types of project management affected the TMS of a team and on the team’s performance. In particular, a comparison was made between a traditional, plan-based approach against an agile method using pair programming. The result demonstrates strong benefits in terms of performance and learning with the agile approach.